1976
DOI: 10.3758/bf03199449
|View full text |Cite
|
Sign up to set email alerts
|

Auditory evoked potentials during selective listening to dichotic speech messages

Abstract: The sensitivity of the scalp-recorded, auditory evoked potential to selective attention was examined while subjects monitored one of two dichotically presented speech passages for content. Evoked potentials were elicited to irrelevant probe stimuli (vowel sounds) embedded in both the right-and the leftear's message. The amplitude of the evoked potential was larger to probe stimuli embedded in the attended message than to probe stimuli in the unattended message. Recall performance was unaffected by the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
4

Year Published

1976
1976
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 5 publications
5
37
4
Order By: Relevance
“…In contrast to previous reports, the attentional modulations observed here did not show the robust N1 effect demonstrated in similar auditory selective attention studies (Sanders et al, 2006; Coch et al, 2005; Woods et al, 1984; Hink & Hillyard, 1976). However, our results are similar to those of Sanders et al (2006), who used a nearly identical experimental procedure and found an emerging but nonsignificant P1 attention effect followed by a sustained N1 effect resembling the Nd component.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to previous reports, the attentional modulations observed here did not show the robust N1 effect demonstrated in similar auditory selective attention studies (Sanders et al, 2006; Coch et al, 2005; Woods et al, 1984; Hink & Hillyard, 1976). However, our results are similar to those of Sanders et al (2006), who used a nearly identical experimental procedure and found an emerging but nonsignificant P1 attention effect followed by a sustained N1 effect resembling the Nd component.…”
Section: Discussioncontrasting
confidence: 99%
“…There has been little reliable evidence, however, that paying attention selectively can modify evoked visual activity prior to 200 msec (Hartley, 1970;Hillyard & Picton, in press). This is in marked contrast to the auditory modality, in which substantial increases of the evoked N. component beginning at 70-90 msec have been related to selective listening to tones or speech messages (Hillyard, Hink, Schwent, & Picton, 1973;Hink & Hillyard, 1976;Schwent & Hillyard, 1975;Schwent, Hillyard, & Galambos, 1976a, 1976bSchwent, Snyder, & Hillyard, 1976c). Eason, Harter, and White (1969) have reported a clear and consistent enhancement of relatively early components of the YEP to flashes at an attended locus in space, with a negative peak at 160-180 msec showing the most dramatic changes.…”
mentioning
confidence: 84%
“…Selective auditory attention has been studied with the help of event-related brain potentials (ERPs). Whether selected on the basis of location or time, attended transient auditory stimuli elicit a N1 that increases in amplitude (Hillyard et al, 1973;Hink and Hillyard, 1976;Näätänen and Picton, 1987;Näätänen and Winkler, 1999) or/and decreases in latency (Folyi et al, 2012;Lagemann et al, 2010;Obleser and Kotz, 2011) as compared with the unattended one. However, not all portions of the unfolding speech signal include abrupt acoustic changes similar to the transient auditory stimuli.…”
Section: Introductionmentioning
confidence: 98%